EFEKTIVITAS PENGGUNAAN METODE DISKUSI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Niken Septantiningtyas; Dea Ayu Rozikin; M Mahbubi (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to explore the application and effectiveness of the discussion method in Islamic Religious Education (PAI) at SMA Negeri 1 Maron, Probolinggo Regency. A qualitative approach with a descriptive research design was used to gain an in-depth understanding of the implementation of the discussion method, its impact on increasing active participation, students' critical thinking skills, and their social skills such as communication and collaboration. Data was collected through direct classroom observation, semi-structured interviews with teachers, and documentation analysis such as lesson plans and teaching materials. The research findings indicate that the discussion method is able to create a more dynamic, dialogical, and inclusive learning environment. Students become more enthusiastic, confident, and able to understand and internalize religious concepts deeply. However, challenges such as the inactivity of some students and the dominance of certain students in discussions still need attention. Therefore, the teacher's readiness and strategy in managing discussions are crucial to its effectiveness. This study makes an important contribution to the development of religious teaching methods that are not only informative but also transformative in shaping students' personalities holistically.